Perancangan User Experience menggunakan pendekatan Human-Centered Design untuk Aplikasi Adopsi Hewan - Dwi Juni Kartika; Herman Tolle; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Pets are animals that live side by side as friends with humans. The large number of abandoned pets is the case in various countries, it is not uncommon for abandoned animals to be found in a sick condition, experiencing violent injuries and even at the end of death. To reduce this, there are people who are willing to help the abandoned animals, but the limited information regarding the abandoned animals makes it difficult for animal helpers to help the abandoned animals. This study aims to design a user experience for animal adoption applications as a solution that can help connect animal owners with potential adopters to facilitate the search for animals that need adoption. The Human Centered Design (HCD) method is used in this research, which will later analyze the context and user needs, design solution designs and evaluate solution designs. The design evaluation on the design of this animal application solution uses usability testing and the User Experience Questionnaire (UEQ) given to 10 respondents. The results of this design evaluation obtained an effective value of 80%, efficiency of 0.108 goals/second, and user satisfaction of 83.25 with grade A and an adjective rating of Excellent. The value of user experience of the design of the solution that is made gets the UEQ value in the excellent category for aspects of attractiveness, efficiency, accuracy, stimulation and novelty. As for the clarity aspect, it gets a good category.